Analisis Kerusakan Jalan Muara Pinang-Muara Payang dengan Metode IRI Menggunakan Aplikasi Smartphone - Sarwandy, Muhammad Hijrah Agung; Yanto, Heri Oki (Jurnal Talenta Sipil, 2026)
The road between Muara Pinang and Muara Payang Villages is severely damaged. Research is needed to assess the level of road service in terms of road surface roughness. The purpose of this study is to analyze the level of road roughness in Muara Pinang and Muara Payang Villages, Empat Lawang Regency, and to provide recommendations for addressing road damage. The method used is the International Roughness Index (IRI) based on the Roadbump Pro smartphone application. The survey was conducted over a 10.5 km stretch, divided into 100-meter segments, using an SUV at a speed of 40-50 km/h. Measurement data showed that most of the road was in the severely damaged category with an average IRI value of 13-14 m/km, indicating poor road surface conditions. These results confirm that the condition of the road pavement at the study site requires serious attention for immediate maintenance and repair. The use of smartphone technology has proven effective and efficient in conducting road condition surveys. Based on the results of the data analysis, the road handling recommendations that must be carried out are improvements or reconstruction.